Zika virus modulates blood-brain barrier of brain microvascular endothelial cells - Ismail, A.A.; Mahboob, Tooba; Samudi, Chandramathi; Sekaran, Shamala Devi (Malaysian Society of Parasitology and Tropical Medicine, 2019)
Zika virus (ZIKV) is a mosquito-borne Flaviviruses. ZIKV is known to cause birth defect in pregnant women, especially microcephaly in the fetus. Hence, more study is required to understand the infection of Zika virus towards human brain microvascular endothelial cells (MECs). In this study, brain MECs were infected with ZIKV at MOI of 1 and 5 in vitro. The changes in barrier function and membrane permeability of ZIKV-infected brain MECs were determined using electric cell-substrate impedance sensing (ECIS) system followed by gene expression of ZIKV-infected brain MECs at 24 hours post infection using one-color gene expression microarray. The ECIS results demonstrated that ZIKV infection enhances vascular leakage by increasing cell membrane permeability via alteration of brain MECs barrier function. This was further supported by high expression of proinflammatory cytokine genes (lnc-IL6-2, TNFAIP1 and TNFAIP6), adhesion molecules (CERCAM and ESAM) and growth factor (FIGF). Overall, findings of this study revealed that ZIKV infection could alter the barrier function of brain MECs by altering adhesion molecules and inflammatory response. © 2019, Malaysian Society for Parasitology. All rights reserved.